Antiviral activity of Momordica charantia: a preliminary study on in vitro anti herpes simplex virus - Praseno, Praseno (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
Traditional medication has been used by Indonesian people since long time ago and still continuing up to the present time. Many of them proved to be effective in curing various diseases. In this study an in vitro activity of Momordica charantia againts Herpes Simplex Virus type 2 has been evaluated by standard method of plaque reduction assay. The aim of this study is to determine whether traditional medicine we are searching has an antiviral activity. The results showed that total inhibition of plaque formation on HSV 2-infected Vero cell line was achieved at concentration of 8% v/v of crude extract, whereas the concentration of 1% v/v was capable of reducing the number of plaques by approximately 50% (inhibitory dose50= ID50). These results were very interesting as even with only small amount of crude extract we could get ID50. We expect that much lower concentration will be required to obtain ID50 if we use purified extract in the assay. Further studies are needed to elucidate other properties of the extract, including its in vivo antiviral activity, possible effect on other viruses, and mechanism of action.Key words: antiviral activity - herpes simplex virus - Momordica charantia - traditional medicine - plaque reduction assay